HUBUNGAN ANTARA PERKEMBANGAN KOTA SOLOK DENGAN PERKEMBANGAN KABUPATEN SOLOK - , Syofia Handayani; , Prof. Ir. Achmad Djunaedi, MUP.,Ph.D., ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Area development both is Province, Regency and Municipality is the integral part, in term very determining the success of national development generally. Solok city and Solok Regency are the two neighboring areas that have close relationship both from their history and their geographical condition, the similarity of their space provide influence to the development of those both area that interrelated and give an impact one to each other. The objective of the study was to explore and describe the relationship that have been being occurred in the development of Solok city with the development of Solok Regency, and to find out the factors that influencing that development relationship. The study approach that was used was mixed methods, where in the qualitative method as a facilitator of the qualitative study. In discussing the development of the Solok city area and Solok Regency, the variables that were observed were area spatial physical aspects, include area topography by observing the altitude and the slope of the area, land use changing, road network and transportation network, population aspect, population growth, population density and distribution and population composition. Economical aspects include area economic growth by considering PDRB, income per capita and analysis of area typology. The result of the study showed that the development that have been being occurred in Solok city gave an impact to the development of Solok Regency especially in the subdistricts which have border directly to the Solok city, such as Kubung Subdistrict, Gunung Talang subdistrict and X Koto Singkarak Subdistrict that can be observed from the high distribution and population density and transformation of business field from primary sector to secondary sector and tertiary sector. The development that have been being occurred in Solok Municipality which had impact to the development of Solok Regency was not occurred in even distribution in the subdistricts in Solok Regency, this caused the imbalance of interaction and economic gap (disparity) amongst subdistricts in Solok Regency.